استخدام مصفوفة كشف التغير في الترشيح متعدد الأزمنة وفي تحليل التغير في صور SAR وPOLSAR للسلاسل الزمنية - بركات, ديمة (Latakia University Journal -Engineering Sciences Series, 2018)
Synthetic Aperture Radar (SAR) satellites and Polarimetric Sar(POLSAR) have provided a tool to draw the Earth surface and generate high-resolution remote sensing imagery. The images which we obtained from SAR have more information we can use it in many things .Thus, this paper introduces a way for analyzing the image time series of SAR and POLSAR which based on change detection matrix (CDM) which contains information about the changed and unchanged pixels. This matrix has been put for each local position in the time series about similar tests. And then the matrix is used to adaptive with the temporal filtering, analyzing of change dynamics. The proposed approach is illustrated on the three following data sets: 25 ascending TerraSAR-X images and 7 descending RADARSAT 2 full polarization images over Chamonix-MontBlanc, France, where the seasonal evolution of glaciers and mountains can be observed, finally time series of 11 ascending ALOS-PALSAR dual polarization images over Merapi volcano, Indonesia during a period including the 2010 eruption. The use of this matrix has resulted in high accuracy results that can be applied to sudden changes in the radar data collection. استخدام مصفوفة كشف التغير في الترشيح متعدد الأزمنة وفي تحليل التغير في صور SAR وPOLSAR للسلاسل الزمنية يستخدم الرادار ذي الفتحة الاصطناعية SAR (Synthetic Aperture Radar)والاستقطابية POLSAR (Polarimetric Sar) لرسم خرائط سطح الأرض حيث يولد صوراً عالية الدقة للاستشعار عن بعد. تحتوي الصور التي يتم الحصول عليها من الرادار على معلومات زائدة عن الحاجة يمكن استخدامها في عدة أمور ولذلك يقدم هذا البحث طريقة لتحليل صور السلسلة الزمنية للرادار بالاعتماد على مصفوفة كشف التغير CDM (Change Detection Matrix) والتي تتضمن معلومات عن البكسلات المتغيرة وغير المتغير. تم وضع هذه المصفوفة من أجل كل موضع مكاني في السلاسل الزمنية عبر اختبارات متشابهة. وقد تم استخدام هذه المصفوفة فيما بعد لتتكيف مع التصفية الزمنية، ولتحليل حركات تغير وكشف التغير متعدد الأزمنة. النهج المقترح تم تطبيقه على ثلاث مجموعات من البيانات ،وهي: صور ال25 تصاعدي لـ TerraSAR-X. كذلك صور 7 تنازلي لـ RADARSAT2 كاملة الاستقطاب فوق شاموني مونت بلانك في فرنسا حيث يمكن مراقبة التطور الموسمي للأنهار الجليدية والجبال. وأخيراً صور 11 تصاعدي لـ ALOS-POLSAR ثنائي الاستقطاب فوق بركان ميرابي في اندونيسيا خلال فترة ثورانه في 2010.وقد أدى استخدام هذه المصفوفة إلى الحصول على نتائج بدقة عالية يمكن تطبيقها على التغيرات المفاجئة التي تحصل على مجموعة بيانات الرادار.